Nutritional Interventions to Improve Immune Function and Reduce Infection Rates in Burn Patients - Liu, Shan; Ji, Geng; Tian, Tian; Chen, Chuanjun; Luo, Binjie (Current topics in nutraceuticals research, 2024)
This prospective interventional study investigated the impact of individualized nutritional interventions on immune function and infection rates in burn patients. This study enrolled 120 burn patients between December 2022 and January 2024. The nutritional interventions focused on protein supplementation, micronutrient replenishment, and inclusion of anti-inflammatory nutrients, specifically omega-3 fatty acids and vitamin C. The nutrients were administered through oral, enteral, and parenteral routes based on dietary preferences and the medical condition of individuals. Protein was prioritized because of its role in leukocyte production; zinc and vitamin C were supplemented to optimize immune function; and omega-3 fatty acids were included to mitigate inflammation and enhance wound healing. The study assessed outcomes through changes in leukocyte and lymphocyte counts, cytokine levels, infection rates, wound healing rates, and the length of hospital stays. Results indicated significant improvements in immune markers and reduced infection rates post-intervention (P < 0.05). Leukocyte count increased significantly, cytokine levels decreased, and the infection rate reduced from 30% to 14.2% (P < 0.05). These outcomes highlighted the efficacy of targeted nutritional interventions in supporting immune health and reducing infections in burn patients. The findings advocated for integrating comprehensive nutritional strategies in managing burn injuries to improve clinical outcomes.